2014
DOI: 10.1007/s10384-014-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adnexal IgG4-related disease: clinical features, outcome, and factors associated with response to systemic steroids

Abstract: Ocular adnexal IgG4-related disease predominantly involved the lacrimal glands bilaterally and was usually associated with high serum IgG4 levels and multiple organ involvement. Most patients responded well to steroid therapy, which was accompanied by a marked decrease in serum IgG4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
0
29
2
Order By: Relevance
“…Sparse eosinophils were observed in only 3 soft tissue biopsies (that did not comprise LG) and obliterative phlebitis was never reported in the present series, as previously published in IgG4-ROD. [6,28] Yet, in all cases, a strict clinicopathologic correlation was performed to rigorously rule out diseases that mimic IgG4-RD, especially those presenting with tumefactive lesions and increased IgG4+ plasma cells on tissue biopsy. Two patients (patients 11 and 12) presented with no extra-orbital manifestations of IgG4-RD and normal serum IgG4 levels, but were included in order not to underestimate the true prevalence of IgG4-ROD or even overlook an entire pattern of patients with strictly localized orbital disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sparse eosinophils were observed in only 3 soft tissue biopsies (that did not comprise LG) and obliterative phlebitis was never reported in the present series, as previously published in IgG4-ROD. [6,28] Yet, in all cases, a strict clinicopathologic correlation was performed to rigorously rule out diseases that mimic IgG4-RD, especially those presenting with tumefactive lesions and increased IgG4+ plasma cells on tissue biopsy. Two patients (patients 11 and 12) presented with no extra-orbital manifestations of IgG4-RD and normal serum IgG4 levels, but were included in order not to underestimate the true prevalence of IgG4-ROD or even overlook an entire pattern of patients with strictly localized orbital disease.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the cause and pathogenesis of BLEL remain unclear. Studies have shown that BLEL belongs to the category of IgG4-related diseases[ 4 5 ]. Clinically, BLEL can be treated with glucocorticoid therapy, but the effects are not ideal.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of enlarged EOMs in thyroid ophthalmopathy is from 80 to 90% [4], and that for IgG4-related ophthalmic disease is 10 to 89% [5, 6]. The incidence of enlarged EOMs is considerably higher for these diseases.…”
Section: Discussionmentioning
confidence: 99%